What does it mean to be a person in law? Ideas from three historical stages in the argentinean legal system - Lell, Helga María (2022)
This paper analyzes the legal concept of person in the Argentinean legal system. The main questions are what does to be a person represents in legal field and which are the images associated to this concept when it comes to recognize certain rights and duties. The paper is structured in three parts: the first one presents the etymology and the metaphor of “person”, the second one focuses on three stages of the concept of person in the Argentinean constitutional history and the third one introduces some nowadays challenges to the concept. There is a contraposition between the mere legal concept (in a positivist way) and a wider legal consideration that involves a moral inspiration. The hypothesis that guides this paper is that the concept of person is unclear in the Argentinean legal system and that it can be redefined in several ways according to the historical stage under study and to the legal context in which it is used.